A critical review of pool and flow boiling heat transfer of dielectric fluids on enhanced surfaces - Leong, Kai Choong (2020)
Pool and flow boiling of dielectric fluids are efficient direct liquid cooling techniques with immense potential in the thermal management of electronic/electrical components. However, due to the increasing demand for higher rate of heat flux dissipation, many enhanced surfaces have been developed to further augment the boiling performance of dielectric fluids. This has resulted in large collections of experimental data and predictive models being reported in the recent years. The present review seeks to consolidate and highlight the recent developments in pool and flow boiling of dielectric fluids on enhanced surfaces. The various models developed to characterize the nucleate boiling curves and to predict critical heat fluxes of plain and enhanced surface are critically examined. The effects of enhanced surfaces on the bubble dynamics in dielectric fluids are also examined and the fundamental studies on boiling found in the recent literature are provided. In addition, attempts are made to categorize the various enhanced surfaces based on their fabrication techniques and their heat transfer performances and to elucidate the thermal transport mechanisms involved. Based on the literature surveyed, the various experimental results are compared, existing shortfalls are identified and areas which require further investigations are proposed.